Prospective Cohort of Fluvoxamine for Early Treatment of Coronavirus Disease 19 - Seftel, David; Boulware, David R (Open forum infectious diseases, 2021)
Abstract We report a real-world experience using fluvoxamine for coronavirus disease 19 (COVID-19) in a prospective cohort in the setting of a mass outbreak. Overall, 65 persons opted to receive fluvoxamine (50 mg twice daily) and 48 declined. Incidence of hospitalization was 0% (0 of 65) with fluvoxamine and 12.5% (6 of 48) with observation alone. At 14 days, residual symptoms persisted in 0% (0 of 65) with fluvoxamine and 60% (29 of 48) with observation. We report a real-world experience using fluvoxamine for early COVID-19. Incidence of hospitalization was 0% (0/65) with fluvoxamine and 12.5% (6/48) with observation alone. At 14 days, residual symptoms persisted in 0% (0/65) with fluvoxamine and 60% (29/48) with observation.